Audience reach of science on television in 10 European countries: An analysis of people-meter data. (February 2016) - Lehmkuhl, Markus; Boyadjieva, Pepka; Cunningham, Yvonne; Karamanidou, Christina; Mörä, Tuomo; ,
Beginning with a differentiation of science programmes into five different editorial concepts, this article explores the audience reach of science on television in 10 European countries with a special emphasis on young audiences aged between 14 and 29 years. In relation to the share of this age group in the entire population, science programmes in all countries reach a considerably smaller proportion of younger viewers. Specific preferences for science content on television do not seem to be relevant in explaining aggregated viewing behaviours especially of young audiences. Unlike all other segments, the young science viewer segment is almost intangible as an aggregated group, as a definable segment of a mass audience that can be targeted by science programme makers.